PYRAMIDING IMPORTANT DISEASE-RESISTANT CHARACTERS BY HYBRIDIZATION OF TRANSGENIC AND NON-TRANSGENIC PEANUTS (ARACHIS HYPOGAEA L.) - Dwi Hapsoro; Hajrial Aswidinnoor; Rusmilah Suseno; . Jumanto; . Sudarsono (Universitas Lampung, 2010)
We have produced transgenic peanut lines carrying a coat protein gene of peanut stripe virus (PStV) and showing resistance to the virus. However, their susceptibility to leafspot disease caused by Cercospora sp. and their lower productivity compared to their genetic background cultivar make them commercially less undesireable. The objective of this research was to test whether crossing the transgenic peanut plants with a non-transgenic peanut line WS, which was resistant to leafspot disease and high-yielding, could produce progenies in F2 generation that were resistant to both PStV and leafspot disease as well as of higher yield campared to their transgenic progenitor. If this test was proven, pyramiding novel transgenic and non-transgenic characters in peanut plants by hybridization would probably be a routine procedure in the future. Crosses were made between transgenic peanut plants that were resistant to PStV and non-transgenic peanut line WS. F2 population was evaluated for resistance to PStV and leafspot disease. Number of filled pods, filled pod dry weight per plant, and dry weight of each pod were measured. Result of the experiment showed that some of the plants in F2 population exhibited resistant both to PStV and leafspot disease and produced higher number of filled pods, filled pod dry weight per plant, and dry weight of each pod compared to those produced by their transgenic parent plants.